Characterization and analysis of ultra wideband signal absorption rates in breast tissues - Mohd Yusoff, Nurul Izzah (2011)
Microwave ultra wideband (UWB) technique has been extensively studied as a potential solution for non-ionizing breast cancer detection. Such technique exploits the significant contrast of dielectric properties between normal tissue and tumour with the exposure of UWB signals where the electric field interacts with biological tissue and produces signatures that can be used to differentiate normal over malignant tissue. This research evaluates the interaction of electromagnetic field with layered breast tissue by a computational method of the Specific Absorption Rate (SAR). SAR analytical model for normal and tumour-affected breast tissues are estimated based on the method. SAR is then evaluated in three dimensional simulations of the normal and tumour-affected breast tissues. Parameters of biological tissues included are defined by Cole-Cole dielectric model. Analysis shows that tumour conductivity gives rise to the characteristic of tissue attenuation. It significantly increases power density in all 1. 5 and 10 mm tumour affected breast tissue compared to normal tissues. However, power density in tumour-affected tissue decreases with the size of tumour as a result of the exponential power degradation as the wave penetrates into the tumour at increasing depths. The absorption rate for normal and tumour-affected breast tissues is predicted by the proposed SAR analytical models. Increase of power density results in the increase of SAR values by 37.29%, 37.44% and 37.59% in 1, 5 and 10 mm tumouraffected breast tissues in comparison with the normal tissues. Evaluation by simulation model is in agreement with that of the proposed analytical model. The study reveals the advantage of the method to interact with a slight change of tissue property which is demonstrated by the increased absorption rate in 1 mm tumour-affected breast tissue as opposed to the normal tissue. The characterization of UWB signal absorption rates by normal and tumour-affected breast tissues further indicates the feasibility of the method for breast cancer detection.